2021
DOI: 10.47264/idea.lassij/5.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Impact of incessant kidnappings on the external relations: A case study of Nigeria

Abstract: Nigeria is a West African country, endowed with a rapidly growing population of over 206 million, with over 500 languages and 250 ethnic groups. It's Africa's most densely populated country and the world's largest black nation. The integration of these complex entities into a unified body has proved difficult since the country's 1914 amalgamation. The government is challenged with violence and military dictatorships, endemic corruption, and abject poverty that intensifies heinous crimes, including kidnapping. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…The statistical analysis conducted for hypothesis one underscores a significant correlation between kidnapping, Calabar carnival and the sustainable tourism development of the Southern Senatorial District in Cross River State, Nigeria (Streimikiene et al, 2021). This conclusion finds support in prior research, including studies by (Yusufu, 2022;Ibrahim et al, 2021;Makua, 2023;Chen et al, 2022). These studies revealed the multifaceted economic impact of kidnapping, encompassing both direct and indirect costs.…”
Section: Discussion Of Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…The statistical analysis conducted for hypothesis one underscores a significant correlation between kidnapping, Calabar carnival and the sustainable tourism development of the Southern Senatorial District in Cross River State, Nigeria (Streimikiene et al, 2021). This conclusion finds support in prior research, including studies by (Yusufu, 2022;Ibrahim et al, 2021;Makua, 2023;Chen et al, 2022). These studies revealed the multifaceted economic impact of kidnapping, encompassing both direct and indirect costs.…”
Section: Discussion Of Resultsmentioning
confidence: 59%
“…The connection between kidnapping and tourism holds grave implications for the tourism industry, which is pivotal for the economic growth of many nations globally. The potential disruption occasioned by kidnapping incidents has the capacity to dissuade tourists from visiting specific destinations, thereby exerting enduring repercussions on the a ffected region's tourism sector (Ibrahim et al, 2021;Eyisi et al, 2021;Kanu et al, 2023). In the same vein, kidnapping incidents can exert severe consequences on tourism sustainability, targeting tourists, tour operators and local residents alike.…”
Section: Literature Review Kidnapping and Tourism Sustainabilitymentioning
confidence: 99%
“…The activities of terrorist groups, bandits, and kidnappers in Nigeria have negatively impacted the country's image both locally and internationally (Demi, 2021). This decline in image has led to several economic consequences, including reduced foreign investment, tourism, and other economic activities (Ibrahim et al, 2021). The damaged image of Nigeria has caused a decline in foreign investment as foreign investors fear losing their investments due to the heightened insecurity in the country.…”
Section: Damage To Nigeria's Imagementioning
confidence: 99%
“…Kidnapping in Nigeria has become a national malaise and source of shame (Olaniyan, 2017). The rampancy of kidnapping for ransom of both foreigners and citizens has flung the Nigerian foreign relations into jeopardy and tarnished her image in the international community (Ibrahim, Ahmad & Shehu, 2021). This negative publicity that kidnapping for ransom attracts to Nigeria has affected trade, tourism and Foreign Direct Investment (FDI) in the country (Okoli & Agada, 2014;Onuohia & Okolie-Osemene, 2019).…”
Section: Impact Of Kidnapping For Ransom On Nigeria's Imagementioning
confidence: 99%